Fully Solution‐Processed n–i–p‐Like Perovskite Solar Cells with Planar Junction: How the Charge Extracting Layer Determines the Open‐Circuit Voltage. Issue 15 (23rd January 2017) - Tao, Chen; Van Der Velden, Jeroen; Cabau, Lydia; Montcada, Nuria F.; Neutzner, Stefanie; Srimath Kandada, Ajay Ram; Marras, Sergio; Brambilla, Luigi; Tommasini, Matteo; Xu, Weidong; Sorrentino, Roberto; Perinot, Andrea; et al.
Abstract : Fully solution‐processed direct perovskite solar cells with a planar junction are realized by incorporating a cross‐linked [6, 6]‐phenyl‐C61‐butyric styryl dendron ester layer as an electron extracting layer. Power conversion efficiencies close to 19% and an open‐circuit voltage exceeding 1.1 V with negligible hysteresis are delivered. A perovskite film with superb optoelectronic qualities is grown, which reduces carrier recombination losses and hence increases V oc .